Corporate Social Responsibility, Corporate Characteristics, and Financial Performance: Evidence from Indonesian Banks - Valentina, Bernadeta; Zaharah, Puteri; Utha, Maria Ariesta (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study examines the relationship between financial success in the Indonesian banking sector, corporate social responsibility (CSR), and corporate characteristics (gender diversity, board size, and firm age). While extensive research has explored the direct impact of CSR on financial performance, fewer studies have examined the effects of corporate characteristics with financial performance, especially in Indonesia. Financial and corporate characteristic data were taken from 13 Indonesian bank’s annual and sustainability reports from 2019 to 2023. Using multiple regression analysis, this study discovered a positive correlation between gender diversity with ROE and firm age with ROA. In contrast, board size and CSR funds have no positive effect on both ROA and ROE.